Overview of the Knowledge of Mothers of Toddlers Who Visit Posyandu Melayu Besar, Rokan Hilir District (Future Science, 2022)
Integrated Healthcare Center (Poyandu) ia a community activity for health services. Every month, mothers who have children under five years old (toddler) should participate in posyandu for their children’s growth and development monitoring. The target of weighing toddler to Posyandu in Indonesia is 85%, while the coverage of toddler weighing in Posyandu Melayu Besar is still below the target. Several impacts like not well educated, toddler would not receive Vitamin A, toddler mother would not understand about growth and development of the toddler would be happen if toddler mother not active bring their toddler to posyandu. Good knowledge about posyandu is needed by every mother who has children under five. Good knowledge will motivate mother for visit to posyandu. This research aimed to describe mother’s knowledge about posyandu. This cross-sectional research was conducted from August to October 2022 in Melayu Besar village, Rokan Hilir, Riau Province. Fifty-five mothers with children 1 – 5 years old were recruited for this study by accidental sampling technique. The data was collected by using questionnaire. This results showed that 60% of participants have good knowledge of posyandu, while the rest have poor knowledge. Mothers with good knowledge were more likely to attend the posyandu every month. Hopefully, the education from health workers will increase motivation of mothers to attend the posyandu. The more often someone gets information through counseling or mass media, then someone’s knowledge will increase.